Labor supply and earnings: In old age, in bad health, and across generations - Anne-Line Koch Helsø (University of Copenhagen, Department of Economics, 2019)
The three largest items on the list of public expenditures in Denmark (and many other countries)are retirement, health, and education. These are also the topics ofi nterest in the three Chapters of this dissertation. While the chapters are quite different from each other, they share three commondenominators. First,as indicated by the dissertation title, they all revolve around the labor supply and earnings of individuals. Second, they seek to shed light on some highly policy-relevant questions. Last, but not least, all chapters are based on the exceptional Danish register data. The three chapters are self-contained with separat eabstracts, bibliographies, and appendices.
Keywords: 330